Over a million students use our free study notes to help them with their homework
Let's open out the bracket using the FOIL method (first, outside, inside, last):
(3 + root(a))(4 + root(a)) = 12 + 3root(a) + 4root(a) + (root(a))2 = 12 + 7root(a) + a.
Since the ...
This is a simple question where students need to use BIDMAS to solve the equation. The easiest method is to seperate the two sides and solve individually, then combine. Firstly, 3(x+5) multiplies out to g...
Anna: 6 bananas. Ben: 6*2.5 = 15 bananas. Callum: (6+15)/3 = 7 bananas Altogether they have 6 + 15 + 7 bananas = 28 bananas
Have you seen anything like this before?
What do you understand by this equation?
How do you expand brackets? Grid/smiles and eyebrows
How confident are you with factors and times ...
Rearrange the first equation to give b as the subject.
b = 16 - 6a
Then substitute that equation for b into the second equation.
5a - 2(16 - 6a) = 19
Simplify this equation (re...
←
648
649
650
651
652
→
Internet Safety
Payment Security
Cyber
Essentials